Aquaporin 2 is differentially expressed in granulosa cells of various stages of human follicles and is regulated by luteinizing hormone - Zheng, Zetong; Tan, Jifan; Chen, Minghui; Zhang, Xiubing; Liu, Simin; Wen, Yangxing; Long, Lingli; Zhou, Canquan; Li, Yubin (Frontiers in Cell and Developmental Biology, 2025)
IntroductionSeveral aquaporins (AQPs) are involved in the influx of water to form follicular fluid, and AQP2 may play a crucial role in follicular growth. However, the specific roles of Aquaporin (AQP) 2 and AQP6 in granulosa cells (GCs) during follicular fluid (FF) formation, as well as their relationship with gonadotropins (Gn), remain unclear.MethodsLuteinized granulosa cells (LGCs) were isolated from follicles of different diameters. Western blot indicated that AQP2 protein levels in LGCs increased as follicles grew larger after luteinization. Immunohistochemistry of human ovarian sections showed that AQP2 levels decreased as follicles progressed from primordial to antral stages. Subsequently, isolated LGCs were treated with varying concentrations of follicle-stimulating hormone (FSH), luteinizing hormone (LH), and estradiol (E2); LH, but not FSH or E2, significantly elevated AQP2 expression. To dissect the underlying signaling pathways, LGCs were further cultured with LH, db-cAMP (a cAMP analog), or forskolin (an adenylate cyclase activator). H89 (a PKA inhibitor) or PD98059 (an ERK1/2 signaling inhibitor) was applied in the presence of LH to evaluate crosstalk between the Gn/cAMP and MAPK cascades.ResultsAQP2 levels in LGCs increased with follicle enlargement after luteinization but decreased as follicles progressed from primordial to antral stages. LH, but not E2, significantly induced AQP2 expression in LGCs in a dose-dependent manner. Forskolin mimicked the stimulatory effect of LH on AQP2 expression. PD98059, but not H89, abolished LH-induced AQP2 up-regulation and inhibited ERK1/2 phosphorylation, indicating potential crosstalk between cAMP and MAPK signaling.DiscussionThis study provides the first evidence for the mechanisms by which AQP2 influences follicular growth and FF formation, highlighting LH-driven, ERK1/2-dependent regulation of AQP2. These findings offer new insights into the ovarian microenvironment and identify potential therapeutic targets for follicle growth disorders.